Jaksa Sebagai Dominus Litis Dalam Optimalisasi Penuntutan Dan Eksekusi Restitusi: Antara Kepastian Hukum Dan Keadilan Substantif Bagi Korban Kekerasan Seksual - Agung Saputra, Rodhi; Anisa Febrianti, Dini (Jurnal Ilmiah Kutei, 2026)
This study provides an in-depth analysis of the role of prosecutors as dominus litis in demanding and executing restitution as a vital instrument for restoring the rights of victims of sexual violence crimes. Although Law Number 12 of 2022 on Sexual Violence Crimes (TPKS Law) has affirmed restitution as a fundamental right of victims, its implementation in practice continues to face serious challenges. This research focuses on the gap between normative promises and practical realities, highlighting the central role of prosecutors as both executors of court decisions and guardians of victims’ rights. The research method employed is normative legal research, using statutory, case, conceptual, and theoretical approaches. The findings indicate that the optimization of the prosecutor’s role is hindered by procedural and institutional constraints, such as the absence of consistent technical guidelines, weak coordination with the Witness and Victim Protection Agency (LPSK), the high workload of prosecutors, the lack of internal standard operating procedures (SOPs) within the Prosecutor’s Office, and sectoral ego among institutions. The availability of substitute penalties that undermine the spirit of victim recovery also constitutes a significant obstacle. A case study, particularly the Herry Wirawan case, reinforces these findings by demonstrating inconsistencies in judicial decisions and a vacuum in the execution of restitution against offenders who are unable to pay. This study concludes that optimizing the role of prosecutors requires a paradigm shift from merely acting as public prosecutors to becoming proactive guardians of victims’ rights. Such a shift must be supported by concrete policy reforms, including the development of clear technical guidelines, strengthened institutional coordination, and the establishment of state-guaranteed mechanisms such as a Victim Trust Fund, as mandated in Article 35 of the TPKS Law.